Hydra: A Vocabulary for Hypermedia-driven Web APls - Lanthaler, Markus; Guetl, Christian (CEUR, 2013)
Coping with the ever-increasing amount of data becomes increasingly challenging. To alleviate the information overload put on people, systems are progressively being connected directly to each other. They exchange, analyze, and manipulate humongous amounts of data without any human interaction. Most current solutions, however, do not exploit the whole potential of the architecture of the World Wide Web and completely ignore the possibilities offered by Semantic Web technologies. Based on the experiences gained by implementing and analyzing various RESTful APIs and drawing from the longer history of Semantic Web research we developed Hydra, a small vocabulary to describe Web APIs. It aims to simplify the development of truly RESTful services by leveraging the power of Linked Data. By breaking the descriptions down into small independent fragments, a new breed of interoperable Web APIs using decentralized, reusable, and composable contracts can be realized.